Immediately loaded anterior single-tooth implants: Two cases - (:unkn) unknown (My University, 2005)
Immediate loading of implants into fresh extraction sockets has the advantage of decreasing the period of healing, reducing the resorption of the alveolar bone, and achieving optimal esthetic results. These cases reveal the clinical success of immediate loaded single-tooth implants placed in fresh extraction sites. Copyright © 2005 by Lippincott Williams & Wilkins.
Keywords: Esthetic; Immediate loading; Implants